2022
DOI: 10.3389/fcimb.2022.841139
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Microbiota and Host-Inflammatory Responses in Periodontitis Affected Individuals With and Without Rheumatoid Arthritis

Abstract: ObjectivesPeriodontitis and rheumatoid arthritis (RA) are two widespread chronic inflammatory diseases with a previously suggested association. The objective of the current study was to compare the oral microbial composition and host´s inflammatory mediator profile of saliva samples obtained from subjects with periodontitis, with and without RA, as well as to predict biomarkers, of bacterial pathogens and/or inflammatory mediators, for classification of samples associated with periodontitis and RA.MethodsSaliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 77 publications
0
18
0
1
Order By: Relevance
“…Escherichia/Shigella is a common oral and intestinal pathogen ( 22 ) also associated with changes in the human microbiome after SARS-CoV-2 infections ( 43 ). Oral Megasphaera was associated with inflammatory illnesses like rheumatoid arthritis and periodontitis ( 44 , 45 ). Their increase might be an indicator for the chronic inflammatory reaction by the damage to the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia/Shigella is a common oral and intestinal pathogen ( 22 ) also associated with changes in the human microbiome after SARS-CoV-2 infections ( 43 ). Oral Megasphaera was associated with inflammatory illnesses like rheumatoid arthritis and periodontitis ( 44 , 45 ). Their increase might be an indicator for the chronic inflammatory reaction by the damage to the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of Sphingomonas was also significantly (p<0.01) higher in the mRANKL_CE group. Eriksson et al (2022) showed that Sphingomonas abundance was positively correlated with RA ( Eriksson et al, 2022 ). Another RA-related genus, Bacteroides , showed decreased abundance in the mRANKL_CE group, although the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Fusobacterium nucleatum ( F. nucleatum ) is a non-spore-forming, anaerobic, gram-negative, pro-inflammatory bacterium, and primarily inhabits the human oral cavity ( 4 ). It has been recognized that F. nucleatum acts as an opportunistic pathogen in multiple inflammatory diseases, including periodontitis ( 5 ), inflammatory bowel disease ( 6 ), liver abscesses ( 7 ), rheumatoid arthritis ( 8 ), and chorioamnionitis ( 9 ). Its involvement in multiple systemic conditions has also been found, such as Alzheimer’s disease ( 10 ), ruptured cerebral aneurysm ( 11 ), atherosclerosis ( 12 ), cardiovascular diseases, adverse pregnancy outcomes, gastro-intestinal disorders, and diabetes ( 13 ).…”
Section: Introductionmentioning
confidence: 99%